Personal Experience of Christ for Catholic Youth (OMK) through IPA (Interpretative Phenomenological Analysis) Approach - Paulus Sih Nugroho (Fakultas Teologi, Universitas Sanata Dharma, 2025)
This article explores the personal experience of Catholic Youth (OMK) with Christ in the context of their daily lives amid contemporary challenges. In a social setting marked by digitalization, value relativism, and spiritual disruption, personal faith experience becomes a vital aspect in shaping the maturity of young people's faith. The aim of this study is to deeply understand how young Catholics experience the presence and relationship with Christ, and how these experiences shape their spirituality and daily faith practice. This qualitative research uses the Interpretative Phenomenological Analysis (IPA) method. Data were collected through in-depth interviews with six youth members from the Parish of Saint Mary Regina Purbowardayan, Surakarta. The findings reveal two major themes: personal relationship with Christ and the embodiment of Christ’s love in real-life actions. Christ is experienced as a companion, healer, and source of strength in life. These experiences form a transformative spirituality that motivates the youth to actively engage in service and witness. In conclusion, the personal experience of Christ serves as a relevant and contextual spiritual resource for youth in facing the challenges of the times and underscores the need for pastoral approaches rooted in lived experience.